İstatistiksel proses kontrolu - Umur, Elvan (Fen Bilimleri Enstitüsü, 2000)
Bu çalışmada, globalleşen dünya içinde, çetin rekabet şartlan altında varlığını sürdürmek isteyen firmalar için vazgeçilmez bir yöntem olan İstatistiksel Proses Kontrol konusu incelenmiştir. Birinci bölümde Toplam Kalite Yönetimi hakkında bilgi verilmiş ve İstatistiksel Proses Kontrolünün tanımı yapılmıştır. Ayrıca İPK'nın Toplam Kalite Yönetimi içindeki yeri, kullanım amaçları, kullanım alanları ve faydalan incelenmiştir. İkinci bölümde bir İPK uygulaması sırasında kullanılacak temel istatistiksel bilgiler ve formüller hatırlatılarak, kalite uygulamalannda en çok kullanılan Temel İstatistiksel Teknikler ele alınmıştır. Üçüncü bölümde ise İPK çalışmalannın en önemli araçlarından biri olan Kontrol Diyagramlan incelenmiştir.Kontrol diyagramlannın çeşitleri, yapısı ve kullanımı ile ilgili bilgiler sunulmuştur. Dördüncü bölümde, prosesin tanımlanması ile başlayan,kontrol altında tutulacak karakteristiklerin belirlenmesi, ölçme aletlerinin seçimi ile devam eden ve makina/proses yeterlilik analizleri ile biten İPK uygulama yöntemi anlatılmıştır. Son bölümde ise tedarikçi-alıcı ilişkilerinde İstatistiksel Proses Kontrolünün yeri ile ilgili bilgi verilmiş, bazı kullanım yerleri açıklanmıştır.

The concept of quality with respect to customer satisfaction has been with us since the human being produces for others. There are two important things for a product and production process. One of them is the cost of the product, which implies the cost of scrap and rework.The other important thing is the quality level of the product.While markets get more global today, both of them are very important for a company. Companies must reduce their costs and increase the level of quality, in order to maintain their market share.If the cost of the product is not low enough or the quality level of the product is not satisfactory, customers don't buy it. In order to increase the quality level and to reduce the costs, some quality tools are needed. One of them and may be the most effective of them is Statistical Process Control. Today each employee at a company must be committed to the use of effective methods to achieve optimum efficiency, productivity and quality to produce competitive goods. Statistical process control (SPC), in its broad sense, is a collection of production methods and management concepts and practices that can be used throughout the organization. SPC involves the use of statistical signals to improve performance and to maintain control of production at higher quality levels. It can be applied to any area where work is done. The statistical concepts that are applied in SPC are very basic and can be learned by everyone in the organization. Production workers must know how SPC applies to their specific jobs and how it can be used to improve their output. Supervisors must be aware of the ways SPC can be used in their sections, be prepared to help their production, workers utilize SPC, and be receptive to suggestions for improvements from the workers who are effectively using SPC. Managers must know how SPC can be used to improve quality and productivity simultaneously. They must create and maintain a management style that emphasizes communication and cooperation between levels and between departments. Their goal must be to develop a working atmosphere that maximizes everyone's contribution to the production of competitive products. XI In the first chapter, information about basic concepts, such as Quality, Quality Control, Total Quality etc. is given. Then definition of statistical process control, its place within TQM, application purposes, application fields and advantages is analyzed. In the second chapter, some basic statistical terms are given. Statistical techniques that are used in quality practices are discussed. In attempting to control any quality characteristic, it is necessary to make observations or measurements that result in numerical data. Whenever numerical data are collected and analyzed for the purpose of making some decisions and of taking some actions, statistical techniques must be used. The most commonly used techniques are the seven basic quality tools, which are: 1. Cause-effect diagram 2.Stratification analysis 3.Check sheet 4.Histogram 5. Scatter diagram ö.Pareto analysis 7.Control charts. Ishikawa states that as much as 95 percent of quality related problems in the factory can be solved with these seven fundamental quantitative tools which are briefly described in this chapter. In the third chapter, control charts are analyzed. Types of control charts, structures of them, applications and comments are presented and the advantages for the users are discussed. Statistical process control charts help us to detect, to diagnose and to correct production problems in a timely fashion. The result is substantial improvement in product quality. On the other hand, control charts also tell us when to leave a process alone, thus preventing unnecessary adjustments that tend to increase the variability of process, rather than reduce it. In addition to detecting the presence of special causes, control charts helps us to estimate the natural tolerance of production process, which in turn permits us to estimate process capability. A natural tolerance is defined as the interval covering ±3 a from the mean of a measured process quality characteristic. Knowing our process capabilities helps us to select the appropriate machines, tools and so on, to meet engineering specifications consistently in our production operations. xn In the fourth chapter, an activity schedule for SPC tool is prepared by using the data handled in the first three chapters. This schedule which begins with the definition of the process, gives the operations to be done for determination of the characteristics to be controlled, selection of the controlling tool and methods or machine and process capability analysis in an order. Capability studies are conducted for the purpose of estimating the process parameters and using this information to determine the ability of the process to meet standards and specifications. If improvement in process capability is possible and economically feasible, then control of the process can be exercised at whatever higher level can be achieved. It would be futile to attempt to establish control of a process at a level that is beyond the capability of an existing process without first improving the process capability. In the fifth and last chapter, the usage of statistical process control at the choice of suppliers is examined since the cost and quality of the material and the half- products bought have a big importance at the product quality and cost.
Statistical process control
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2000
Keywords: Yeterlilik; İstatistiksel süreç kontrol; Sufficiency; Statistical process control